Stress analysis on braided composites - Ong, Shee Yin. (2011)
Since the 1940s, fiber reinforced polymer (FRP) composites have revolutionized aerospace technologies and gained escalating attention, driving numerous research objectives. In recent years, three-dimensional (3D) fiber structures have been developed due to increasing demands of FRP materials in load-bearing aircraft structures requiring high impact damage tolerance and improved through-thickness mechanical properties. Braiding was the first textile process used to manufacture 3D fiber preforms. But in spite of demonstrated advantages in versatility and impact performance, adoption of braided composites have been limited by the maturity of textile braiding processes and the understanding required to design and cost-effectively manufacture a preform for a specific application. This final year project focuses on the analyses of braided preforms during its fabrication on both a microscopic and macroscopic scale. In this study, stress fields of preforms at intervals of braiding process are analyzed through finite element methods. The influence of braid parameters on stress fields is also investigated by comparing between a preform designed with fixed yarn gap and that designed with controlled angles. Additionally, the micro-mechanical properties of respective preforms are determined by deriving representative unit-cell models and unit-cell properties are evaluated. Experimental data demonstrates trends of in-plane Young’s Modulus variation with braid angle and yarn gap. Additionally, observations of increased stresses as preforms lengthen suggest needs to monitor and control braiding speeds. Lastly, it is concluded that the ideal design for a braided composite of wide diameter range, recommends fixed braid angles below 35o at small diameters, while larger diameters favor a constant yarn gap size that yields high braid density. As a roundup of the author’s project, recommendations for future works to include previously neglected parameters are discussed.